Effect of autologous platelet rich plasma on thin endometrium in frozen thawed embryo transfer - Anitha, Adaboina; Rani, Burri Sandhya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Endometrium is one of the main factors in implantation and pregnancy. Some of the assisted reproductive technology treatment (ART) cycles get cancelled due to inadequate endometrial growth. This study was conducted to evaluate the effectiveness of PRP (platelet rich plasma) in the treatment of thin endometrium and its outcome on pregnancy and live birth rates. Methods: This study was a prospective cohort which was conducted from January 2018 to December 2018 at Laxmi Narasimha Hospital, Warangal, Telangana State. 30 patients with history of inadequate endometrial growth in frozen thawed embryo transfer cycles were recruited into the study. Intrauterine infusion of PRP was performed. Endometrial thickness was assessed. Results: 30 women were recruited in the study data of the 24 women were collected. Live birth was seen in 5 patients in the week range of 37±to 37±5 and average EMT in mm was 7.8, abortion was seen in 3 patients in the week range of 6 to 8±2 and average EMT in mm was 7.4 , chemical pregnancy was seen in 2 patients in the week range of 6 and average EMT in mm was 7.2 and number of women who were not pregnant were 14 and average EMT in mm was 7.0. Live birth was observed in 21% of the patients, abortion was observed in 13%, chemical pregnancy was seen in 9% and women who were not pregnant were 58%. Conclusions: Ability of autologous PRP to restore the endometrial receptivity of damaged endometrium has some aspects other than increasing the EMT.